In Vitro Bulb Regeneration from Stem Explants of Endemic Geophyt Muscari aucheri (Boiss.) Baker - Kutlu, Mehmet Ali; Kılıç, Ömer; Bagcı, Eyüp (My University, 2017)
Muscari aucheri (Boiss.) Baker bears beautiful and attractive purplish blue flowers bloom between May and June; it grows stony slopes, mountain pastures an altitude of 1000-3000 meters. The natural populations of Muscari aucheri, is seriously affected by increased environmental pollution, urbanization and grazing. Therefore, this study aimed to accelerate multiplication by devising a strategy for an efficient in vitro bulblet regeneration system of Muscari aucheri using stem explants on MS medium containing 1, 3, 5 mg/l TDZ plus 0, 0.1, 0.2, 0.4 mg/l NAA (12 combinations). The stem explants induced direct bulblet regeneration on explants. Maximum mean number of bulblets per explant was noted on MS medium containing 3 mg/l TDZ + 0.4 mg/l NAA and maximum mean number of bulb diameter was noted on MS medium containing 5 mg/l TDZ + 0.2 mg/l NAA. The regenerated bulblets were isolated from stem explants and cultured on MS medium containing 40 g/l sucrose; where they gained diameter and rooted.
Keywords: Biyoloji; Genetik ve Kalıtım